2012
DOI: 10.1002/cbdv.201200024
|View full text |Cite
|
Sign up to set email alerts
|

Melanogenesis‐Inhibitory and Cytotoxic Activities of Diarylheptanoids from Acer nikoense Bark and Their Derivatives

Abstract: Nine cyclic diarylheptanoids, 1-9, including two new compounds, i.e., 9-oxoacerogenin A (8) and 9-O-β-D-glucopyranosylacerogenin K (9), along with three acyclic diarylheptanoids, 10-12, and four phenolic compounds, 13-16, were isolated from a MeOH extract of the bark of Acer nikoense (Aceraceae). Acid hydrolysis of 9 yielded acerogenin K (17) and D-glucose. Two of the cyclic diarylheptanoids, acerogenin A (1) and (R)-acerogenin B (5), were converted to their ether and ester derivatives, 18-24 and 27-33, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Although the authors did not report any biological tests, this plant together with the sister species C. comosa are known to be rich sources of diarylheptanoids (e.g. Curcumin, 253 ) [ 193 , 194 ], which are known for their antioxidant [ 195 ], antiviral [ 196 ], melanogenesis-inhibitory and cytotoxic [ 197 200 ], anti-Leishmanial [ 201 ] and anti-Trypanosomal [ 202 ] activities, just to mention these ones.…”
Section: Zingiberaceae and Zygophyllaceaementioning
confidence: 99%
“…Although the authors did not report any biological tests, this plant together with the sister species C. comosa are known to be rich sources of diarylheptanoids (e.g. Curcumin, 253 ) [ 193 , 194 ], which are known for their antioxidant [ 195 ], antiviral [ 196 ], melanogenesis-inhibitory and cytotoxic [ 197 200 ], anti-Leishmanial [ 201 ] and anti-Trypanosomal [ 202 ] activities, just to mention these ones.…”
Section: Zingiberaceae and Zygophyllaceaementioning
confidence: 99%
“…japonica led to the isolation of an arylbutanoid glycoside, (2R)-4-(4-hydroxyphenyl)-2-butanol 2-O-β-D-apiofuranosyl-(1→6)-β-D-glucopyranoside (BAG). In previous pharmacological studies, BAG showed significantly inhibitory activity on lipid peroxidation as well as α-tocopherol, BHA and BHT [18] and also exhibited melanogenesisinhibitory activity with no toxicity to the B16 melanoma cells [19]. BAG was reported to show remarkable inhibitory activity against the degranulation of RBL-2H3 by antigen stimulation, which can potentially be used for the treatment of IgE-FcεRI interaction-related allergic disorders [20].…”
Section: Introductionmentioning
confidence: 97%
“…1) A variety of phenolic compounds including diarylheptanoids, [2][3][4][5][6][7][8][9][10][11] phenylbutanoids, 4,12) coumarinolignans, 13) neolignans, 14) tannins 15) and flavonoids 12) have been reported as the constituents of A. nikoense. Some of these compounds show various biological activities such as anti-oxidant, 16) anti-inflammatory, 9) hepatoprotective, 17) osteogenic, 18) vasorelaxant, 19) melanogenesis inhibitory, 11,16) nitric oxide (NO) production inhibitory 8,20) and sodium glucose cotransporter (SGLT) inhibitory activities. 10) We have been investigating edible and medicinal plants effective for the suppression of genotoxicity to discover new chemopreventive agents.…”
mentioning
confidence: 99%